Investigation and Study of CaO-Borate Glass - Priya, D.; Thirumaran, S. (Physics and Chemistry of Solid State, 2021)
Recent days the special interest towards Glasses is specifically due to their vast applications that they range. Glass series Calcium borate metallic glass (CaO–B2O3) has been prepared by melt quenching technique. CaO influences like density/molar volume ratio on the properties have analyzed and glass sample different modulus has found between them. The optical properties such as direct and indirect bandgap, Urbach energy, band gap, which also includes heat‐treated glasses, has studied by Fourier transform infrared spectroscopy and UV‐visible, respectively. According to this model elastic moduli increase, this is because of the CaO content increase. The Debye temperature, elastic moduli, other acoustic parameters and Poisson's ratio has acquired from experimental data. The obtained results show that the CaO enters into the glass network as a modifier by occupying increasing the nonbridging oxygen atoms (NBOs) and the interstitial spaces in the network.